If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -63 + -4x = 135 + 7x Solving -63 + -4x = 135 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -63 + -4x + -7x = 135 + 7x + -7x Combine like terms: -4x + -7x = -11x -63 + -11x = 135 + 7x + -7x Combine like terms: 7x + -7x = 0 -63 + -11x = 135 + 0 -63 + -11x = 135 Add '63' to each side of the equation. -63 + 63 + -11x = 135 + 63 Combine like terms: -63 + 63 = 0 0 + -11x = 135 + 63 -11x = 135 + 63 Combine like terms: 135 + 63 = 198 -11x = 198 Divide each side by '-11'. x = -18 Simplifying x = -18
| 8=4-3b+1 | | 500+35*X=55*x | | -4n+2(-7n-5)=-7n+1 | | y^2=-4x^2+8x-3 | | X+36x=130 | | (x^2)-6x=1 | | -39-6b=-5(b+8) | | (4w^2)+12w+9=49 | | 3x=11x+25 | | -9cosx-3sinx=0 | | -9(k-1)=6-5(3k+3) | | 6(-4n-8)=96 | | -3n-5=-23 | | 8v+5=11 | | -4(-6b-4)=208 | | 7(7-12n)=-12n-11(n-10) | | 19(8c-1)-8=150c+19 | | 5x+8=7+3m | | 2+6a=-4+7a | | .06(x-.5)=.06x+0.01 | | -5(n+5)=2(8n-2) | | 1.2+6=9.6 | | 27x^3-147x=0 | | Yk-yz=t | | 5x+6x-2=53 | | 5x+8=7+m | | 7-5n=n+3-2n | | -16-16+8=-8-16 | | -19n+1=-18n-5 | | 29=a^2+3a-1 | | 90=(x-(90-x))+74 | | -2(x-1)=2x+3 |